2016
DOI: 10.3748/wjg.v22.i10.3023
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver indexvswaist circumference for predicting non-alcoholic fatty liver disease

Abstract: Although FLI had acceptable discriminatory power in the diagnosis of NAFLD, WC was a simpler and more accessible index with a similar performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 32 publications
11
69
3
1
Order By: Relevance
“…In contrast with our study, Motamed et al suggested higher cut-off values of FLI for females because of the protective effect of estrogen in females (11).…”
Section: U N C O R R E C T E D P R O O Fcontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast with our study, Motamed et al suggested higher cut-off values of FLI for females because of the protective effect of estrogen in females (11).…”
Section: U N C O R R E C T E D P R O O Fcontrasting
confidence: 99%
“…Our findings indicated that the FLI has a good performance in predicting NAFLD with an AUC of 0.84, based on controlled attenuation parameter (CAP) detection, which was in line with the results of a baseline cohort study in Iran that showed FLI has a good predicting power in the diagnosis of NAFLD, with an AUC of 0.865; however, in this cohort study, ultrasound was used for diagnosis of NAFLD (11). Also, in another study by Xiaolin Huang on 8626 Chinese adults, the AUC of FLI was 0.834 for predicting NAFLD (20).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nonalcoholic fatty liver disease (NAFLD) is one of the most common liver diseases around the world (1,2) and its prevalance has grown due to unhealthy life styles (3). The disease has a wide spectrum from simple steatosis to nonalcoholic steatohepatitis (NASH), which is hepatic steatosis accompanied by inflammation or liver cell injury with or without fibrosis (4).…”
Section: Introductionmentioning
confidence: 99%